2004
DOI: 10.1196/annals.1294.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signaling of Somatostatin Receptors

Abstract: Somatostatin is a neuropeptide family that is produced by neuroendocrine, inflammatory, and immune cells in response to different stimuli. Somatostatin acts as an endogenous inhibitory regulator of various cellular functions including secretions, motility, and proliferation. Its action is mediated by a family of G-protein-coupled receptors (called sst1-sst5) that are widely distributed in the brain and periphery. The five receptors bind the natural peptides with high affinity, but only sst2, sst5, and sst3 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 66 publications
1
96
0
7
Order By: Relevance
“…The binding of hormone to somatostatin receptors initiates a complex set of signaling events triggered by the interaction of the activated receptors with a large number of different protein partners (for recent reviews see (Csaba and Dournaud, 2001;Lahlou et al, 2004;Olias et al, 2004;Schonbrunn, 2004), reviews in this compendium). As members of the seventransmembrane domain receptor family, it is not surprising that much of somatostatin receptor signaling involves activation of heterotrimeric G proteins.…”
Section: Somatostatin Receptor Signaling and Regulation Involve Multimentioning
confidence: 99%
“…The binding of hormone to somatostatin receptors initiates a complex set of signaling events triggered by the interaction of the activated receptors with a large number of different protein partners (for recent reviews see (Csaba and Dournaud, 2001;Lahlou et al, 2004;Olias et al, 2004;Schonbrunn, 2004), reviews in this compendium). As members of the seventransmembrane domain receptor family, it is not surprising that much of somatostatin receptor signaling involves activation of heterotrimeric G proteins.…”
Section: Somatostatin Receptor Signaling and Regulation Involve Multimentioning
confidence: 99%
“…In particular, SS inhibits pituitary GH and TSH secretion and insulin, glucagon, and secretin secretion at gastro-entero-pancreatic level (Van Op den Bosch et al 2009, Reubi & Schonbrunn 2013. These effects are mediated by five receptor subtypes (SST1-5) belonging to the G protein coupled receptors superfamily (GPCR) that differ in tissue distribution, affinity to ligands and mechanisms of action and regulation (Patel 1998, Lahlou et al 2004. As demonstrated in cells transfected with different receptor subtypes and confirmed by the clinical use of selective agonists, SST2 and to lesser extent SST5 and SST3 appear to mediate most of the antisecretive and antiproliferative effects of SS (Reubi & Schonbrunn 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological responses vary with the expression of individual receptor subtypes that are functionally coupled to the effectors of signal transduction, resulting in physiological impact. 20 Within the context of this study, SSTR4 was uniquely expressed by HOCs within the liver. The expression of SSTR4 in rat liver has not been observed previously.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin receptors (SSTRs) are widely distributed throughout many tissues and show different functions in various cell and tissue types. 18,20 However, studies on receptor expression in various tumors reveal inconsistencies, which are also observed in rat liver studies. 21,22 Reynaert et al 22 reported the presence of SSTRs 1-3 in activated hepatic stellate cells in CCl 4 -treated rats, but not in normal rat liver.…”
mentioning
confidence: 97%